2004
DOI: 10.1021/om0499198
|View full text |Cite
|
Sign up to set email alerts
|

Silver(I) Scorpionate Mediated Insertion of Carbenes into Aliphatic C−H Bonds

Abstract: Silver(I) adducts featuring highly fluorinated tris(pyrazolyl)borate, [HB(3,5-(CF3)2Pz)3]-, catalyze the carbene insertion into carbon−hydrogen bonds of cyclic and acyclic hydrocarbons at room temperature. These silver complexes are more effective than related copper catalysts such as [HB(3,5-(CF3)2Pz)3]Cu(THF) for hydrocarbon activation via this route.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(76 citation statements)
references
References 25 publications
2
73
1
Order By: Relevance
“…[20][21][22][23] In particular, several nonradical oxidative group-transfer reactions catalyzed by silver were discovered. [24][25][26][27] We reported a disilver(i) compound (1, Scheme 1 a) that efficiently catalyzes the aziridination of olefins. [26] Surprisingly, subsequent studies showed that only this disilver complex gave clean aziridine products in the silver-mediated reactions tested with a variety of different ligands.…”
mentioning
confidence: 99%
“…[20][21][22][23] In particular, several nonradical oxidative group-transfer reactions catalyzed by silver were discovered. [24][25][26][27] We reported a disilver(i) compound (1, Scheme 1 a) that efficiently catalyzes the aziridination of olefins. [26] Surprisingly, subsequent studies showed that only this disilver complex gave clean aziridine products in the silver-mediated reactions tested with a variety of different ligands.…”
mentioning
confidence: 99%
“…For example, in 2004, Dias, Lovely, and coworkers reported early examples of carbene insertion into sp 3 C-H bond of alkanes and ethers by silver with tris (pyrazolyl)borate complex 1 [18,19]. In this reaction, using neat alkane as substrate ]Ag(THF) 1 as catalyst (Scheme 1), and ethyl diazoacetate (EDA) as a carbene source, the desired carbene insertion products were observed with moderate to excellent yield (41-88%, Scheme 3).…”
Section: Direct C-c Bond Formationmentioning
confidence: 99%
“…Similar detrimental effects of the presence of an 70 oxygen in -position had been observed in the enantioselective insertion of methyl phenyldiazoacetate into both crown ethers and 1,2-dimethoxypropane with Rh catalysts, 21 and in the nonenantioselective insertion of ethyl diazoacetate into 1,4-dioxane with homogeneous copper 5b and silver scorpionates. 22 The 75 presence of a second oxygen in -position was tested in the case of 1,3-dioxolane. In principle position 2 in this substrate is more activated, due to the presence of the two adjacent oxygen atoms.…”
Section: Catalytic Activity In C-h Insertion (Chemoselectivity)mentioning
confidence: 99%